ANALISIS PERBANDINGAN KINERJA KEUANGAN BANK KONVENSIONAL DAN BANK SYARIAH (Periode 2012-2014) - Syaidina Efri Saputra; Emrinaldi Nur DP; Yuneita Anisma (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2016)
This study aimed to compare the financial performance of conventional banking with Islamic banking in the period 2012-2014 by using financial ratios. Financial ratios used consisted of Capital (CAR), Assets (NPL/NPF), Earnings (ROA, NIM/NOI and BOPO), and Liquiduty (LDR/FDR). The population in this research is 118 companies conventional banking and 11 companies Islamic banking which are listed Bank of Indonesia during the period of 2012-2014 while the amount of the research samples are 20 banks, is 10 conventional banks and 10 islamic banks. This study using hypothesis testing the "Independent Sample t-Test" to see the difference in the financial performance of Islamic banking with conventional banking as a whole. The results showed that Assets (NPL/NPF) and Earnings (NIM/NOI) do not differ significantly between Islamic banks with the conventional banks, Capital (CAR), Earnings (ROA and BOPO) and Liquidity (LDR/FDR) that showed significant differences between Islamic banking and conventional banking. The signifiant value of the Capital Adequacy Ratio (CAR) 0.016, Non Performing Loan/Non Performing Financing (NPL/NPF) 0.055, Return On Assets (ROA) 0.015, Net Interest Margin/Net Operating Income (NIM/NOI) 0,504, Biaya Operasional terhadap Pendapatan Operasional (BOPO) 0.006, and Loan to Deposit Ratio/Financing to Deposit Ratio (LDR/FDR) 0.000.Keywords : CAR, NPL/NPF, ROA, BOPO